2011
DOI: 10.1159/000322879
|View full text |Cite
|
Sign up to set email alerts
|

Two Newly Identified Cat Allergens: The von Ebner Gland Protein Fel d 7 and the Latherin-Like Protein Fel d 8

Abstract: Introduction: Characterization of the complete IgE binding spectrum of cat allergens is important for the development of improved diagnosis and effective immunotherapeutics. While Fel d 1 remains unchallenged as the major cat allergen, we now report the isolation of two new allergens capable of binding similar concentrations of IgE in the allergic sera of some individuals. Materials and Methods: Cat tongue and submandibular salivary gland cDNA libraries were screened by DNA hybridisation and IgE immunoassay. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 71 publications
(68 reference statements)
1
53
0
Order By: Relevance
“…A latherin-like allergen protein has also been characterized from the tongue epithelium and salivary glands of cats (Fel d 8; [14]). Whether latherin and its relatives are intrinsically allergenic, or become targets of allergic responses in certain individuals responding coordinately to other allergenic stimuli, remains to be seen.…”
Section: Introductionmentioning
confidence: 99%
“…A latherin-like allergen protein has also been characterized from the tongue epithelium and salivary glands of cats (Fel d 8; [14]). Whether latherin and its relatives are intrinsically allergenic, or become targets of allergic responses in certain individuals responding coordinately to other allergenic stimuli, remains to be seen.…”
Section: Introductionmentioning
confidence: 99%
“…We have focused on these two genes as they have both been independently studied by a number of groups [8,9,14,15,16]. Table 1 also clearly shows that two other genes, BPIFA3 (SPLUNC3) and Bpifa6 (Splunc6), diverge significantly from our rules, but at this time these two have not been studied at all.…”
Section: Genementioning
confidence: 87%
“…We showed that BPIFA4 is a SPLUNC and that its closest paralogue at the time was horse latherin (GenBank ® accession number AF491288) which is 42 % identical [5,15]. The gene appears to be absent from the rodent lineage, but has been identified in cows and cats [5,6,10,16]. The predicted protein product of human BPIFA4 is significantly shorter than other single-domain-containing proteins and appears to be missing approximately 50 amino acids from the C-terminal end of the molecule, including the cysteine residue that is conserved in all other family members [4,5].…”
Section: Bpifa4 (Base)mentioning
confidence: 96%
“…This may have generated the idea that understanding mammalian allergens is basically simple -lipocalins, secretoglobins and serum albumins, and possibly also cystatins [13] and latherins [14,15] -if you know these few protein families, you may think you know it (almost) all. However, having now much more precise information than we may have wished for, we are facing new questions, some of which were quite unexpected.…”
Section: Developments In Technologies For the Characterization Of Allmentioning
confidence: 99%